2010
DOI: 10.2169/internalmedicine.49.3660
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Therapeutic ERCP for the Elderly with Choledocholithiasis: Comparison with Younger Patients

Abstract: Objective To clarify the efficacy and safety of therapeutic endoscopic retrograde cholangiopancreatography for the elderly with choledocholithiasis compared with younger patients. Methods Consecutive therapeutic ERCPs performed between 2005 and 2007 at our institution for 118 patients aged 80 years or older (group A) and 205 patients younger than 80 years old (group B) were retrospectively reviewed. Successful cannulation rate, complete stone clearance rate, complications and prognosis were compared between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
5
21
0
3
Order By: Relevance
“…Because of these significant potential complications, appropriate patient selection is important in the provision of safe ERCP. Our group and others have looked at age as a predictive factor in potential adverse outcomes and found that age alone should not be a determinant in withholding ERCP . Initial outcomes are at least equivalent to a younger cohort.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Because of these significant potential complications, appropriate patient selection is important in the provision of safe ERCP. Our group and others have looked at age as a predictive factor in potential adverse outcomes and found that age alone should not be a determinant in withholding ERCP . Initial outcomes are at least equivalent to a younger cohort.…”
Section: Introductionmentioning
confidence: 84%
“…Our group and others have looked at age as a predictive factor in potential adverse outcomes and found that age alone should not be a determinant in withholding ERCP. 4,5 Initial outcomes are at least equivalent to a younger cohort. A recent Canadian study found that age was associated with longer procedure times.…”
Section: Introductionmentioning
confidence: 99%
“…Two cases had perforations, one had a hemorrhage and one had pacreatitis. T. Obana et al, have observed no mortalities connected to the ERCP procedure [15]. However, low that it may be, ERCP has a mortality rate of 0.7% -0.9% [16].…”
Section: Discussionmentioning
confidence: 97%
“…La sphinctérotomie endoscopique est particulièrement indiquée chez les malades âgés fragiles avec ou sans antécédent de cholécystectomie ayant une LVP compliquée. L'incidence et la prévalence des complications sont identiques à celles rencontrées chez le sujet plus jeune [31]. Katsinelos et al [32] ont montré des taux très faibles de complications post-CPRE thérapeutiques chez le sujet de 80 ans et plus.…”
Section: Cholécystite Aiguëunclassified